Herschel-ATLAS and ALMA: HATLAS J142935.3-002836, a lensed major merger at redshift 1.027 - Messias, Hugo; Dye, S.; Nagar, Neil; Orellana, Gustavo; Shane Bussmann, R.; Calanog, Jae; Dannerbauer, Helmut; Fu, Hai; Ibar, Edo; Inohara, Andrew; Ivison, R.J.; Negrello, Mattia; et al. (EDP Sciences, 2014)
Context. The submillimetre-bright galaxy population is believed to comprise, aside from local galaxies and radio-loud sources, intrinsically active star-forming galaxies, the brightest of which are lensed gravitationally. The latter enable studies at a level of detail beyond what is usually possible by the observation facility.